Pengaruh Progressive Muscle Relaxation (PMR) Terhadap Fatigue Pasien Kanker Payudara Yang Menjalani Kemoterapi - Sri Riwayati; Musa’adah Musa’adah; Dwi Fitriyanti (Jurnal Anestesi, 2024)
Breast cancer occurs due to abnormal, uncontrolled, and irregular cellular growth in the breast. The management of breast cancer includes surgery, chemotherapy, radiation therapy, hormonal therapy, immunotherapy, and bone marrow manipulation. The physical impacts of chemotherapy include sleeping problems and fatigue. The non-pharmacological efforts to relieve this fatigue include progressive muscle relaxation (PMR). The research objective was to determine the effect of Progressive Muscle Relaxation (PMR) on the level of fatigue in breast cancer patients undergoing chemotherapy. The research design was a pre-experimental one group pre-posttest design. The population is breast cancer patients undergoing chemotherapy as many as 35 patients. The number of respondents is 35 respondents. The sampling technique used is total sampling. The research instrument used is the Fatigue Assessment Scale (FAS). The test used is the Wilcoxon test. The results showed that there was an effect of Progressive Muscle Relaxation (PMR) on the level of fatigue in breast cancer patients undergoing chemotherapy with a p value = 0.000 (<0.05). The research recommendation is Progressive Muscle relaxation (PMR) intervention as a non-pharmacological intervention to reduce the fatigue level of breast cancer patients undergoing chemotherapy in health services.